The Impact of E-Government on Social Inclusion: A Bibliometric Review of E-Inclusion Research - Perdana, Gusti Naufal Rizky; Arintyas, Ameylia Puspita Rosa Dyah Ayu; Syari, Suci Fitrah; Wilmantara, Gilang (Jurnal Pemerintahan dan Politik Lokal, 2025)
This study explores the intersection of e-government and social inclusion through a bibliometric analysis of e-inclusion research. Drawing on 97 publications indexed in Scopus, the analysis was conducted using VOS viewer and NVivo 12 Plus to identify research trends, dominant themes, and collaborative networks among scholars, institutions, and countries. The findings reveal that e-government plays a critical role in promoting inclusive governance by enhancing digital access, participation, and service delivery. However, challenges such as the digital divide and unequal digital skills continue to hinder broader social inclusion. Thematic clusters identified include empowerment, accessibility, digital literacy, and trust. Developed and developing countries alike contribute to this field, although research remains uneven. This study offers valuable insights into the evolving discourse on e-inclusion and highlights gaps for future exploration. The findings are intended to inform policymakers, scholars, and practitioners in designing more equitable and inclusive digital governance frameworks.